Recognizing the gift : toward a renewed theology of nature and grace - Rober, Daniel A. (Emerging scholars., 2016)
Recognizing the Gift puts twentieth-century Catholic theological conversations on nature and grace, particularly those of Henri de Lubac and Karl Rahner, into dialogue with Continental philosophy, notably the thought of Jean-Luc Marion and Paul Ricoeur. It thus argues for a theology of nature and grace in terms of recognition of the gift, drawing out the reciprocal and political nature of recognition in opposition to those, including Marion, who would seek to avoid politics and reciprocity as a proper avenue of inquiry for theology.